The detrimental impact of low birth rates on Malaysia's accelerated transition to an aged society - Nadarajan, Jeeveintheren; Borhan, Muhammad Haziq; Sharil Idrus, Muhamad; Daniel Abdullah, Muhammad Fariedz; Ab Hamid, Muhammad Nabil; Rosnon, Mohd Roslan; Abdul Razak, Muhammad Afiq; Kunasekaran, Puvaneswaran; Ibrahim, Rahimah (Human Resource Management Academic Research Society, 2024)
As Malaysia transitions towards becoming an ageing society, it faces numerous challenges that require comprehensive and strategic responses. The rapid demographic shift with a significant rise in the number of people over 65 brings about paradigm changes in various aspects of society. As Malaysia experiences this rapid increase in its elderly population driven by a low birth rate, it faces significant challenges in various sectors. The method used in this paper is concept mapping which allow the authors to analyze the existing literature towards finding a pattern of variables. Existing research highlights that low birth rates in Malaysia are influenced by income levels, demographic shifts, and climatic conditions. These factors collectively contribute to the increasing proportion of elderly individuals. This study identifies six key issues related to Malaysia's ageing population, focusing on healthcare needs, financial security, social isolation, caregiver support, infrastructure and policy implications and then proposes strategic responses to address these challenges.